The International Standard Classification of Education (ISCED) - Bohlinger, Sandra [Verfasser] (My University, 2013)
"The original purpose of the International Standard Classification of Education (ISCED) was solely to facilitate standardised international comparisons of statistics across education systems. Over the course of decades it proved so useful that, more recently, it has also been invested with an evaluative function and treated as a reference standard which informs the development of new qualifications, qualification frameworks or entire education systems. Nevertheless, it only gives a limited reflection of the reality within education systems and the diversity of existing qualifications, and even the new version of ISCED approved at the end of 2011 in no way alters that fact. The aim of the article is therefore to understand the underlying basis of the ISCED classification and the comparative scales and values that may be used to map a qualification to a level. Ambiguities mainly arise at the point where a qualification’s valence, in the sense of rigour and complexity of content, justifies the mapping of a qualification to a particular level." (Autorenreferat, BIBB-Doku)
Keywords: Klassifikation; ISCED; Berufliche Qualifikation